Coloring zirconium oxide for novel energy saving industrial applications. (May 2022) - Silvestroni, Laura; Capiani, Claudio; Sciti, Diletta; Sani, Elisa
Abstract: White conventional zirconium oxide was mixed to black or rust coloring second phase additives to increase the absorptance and thermal emittance with the aim of exploring novel oxide-based ceramics for energy exploitation and saving, like solar absorbers or even industrial refractory kiln walls. The variation of the optical properties of the colored samples was evaluated as a function of the amount, dopant type and co-doping and it was found that notable changes to the optical spectrum occur already upon introduction of 0.05 wt% pigment. The absorptance of ZrO2 passed from 0.1, in the white ceramic, to 0.75, for the rust-colored ones, and up to 0.82, for black colored materials containing Co-oxide as additive. The thermal emittance and solar absorptance of the black/rust-shaded specimens were calculated for temperatures from 400 to 1500 K and compared to commercial white, black and brown reference to identify the most appropriate composition for the two proposed applications and operating temperatures. Graphical abstract: Image 1